Oligo-Carrageenan Kappa-Induced Reducing Redox Status and Increase in Trr/Trx Activities Promote Activation and Reprogramming of Terpenoid Metabolism in Eucalyptus Trees - Moenne-Munoz, A; Gutierrez-Cutino, M; Gutierrez-Cutino, M; Gonzalez-Figueroa, A (Multidisciplinary Digital Publishing Institute (MDPI), 2014)
In order to analyze whether the reducing redox status and activation of thioredoxin reductase (TRR)/thioredoxin(TRX) system induced by oligo-carrageenan (OC) kappa in Eucalyptus globulus activate secondary metabolism increasing terpenoid synthesis, trees were sprayed on the leaves with water, with OC kappa, or with inhibitors of NAD(P)H, ascorbate (ASC) and (GSH) synthesis and TRR activity, CHS-828, lycorine, buthionine sulfoximine (BSO) and auranofine, respectively, and with OC kappa and cultivated for four months. The main terpenoids in control Eucalyptus trees were eucalyptol (76%), á-pinene (7.4%), aromadendrene (3.6%), silvestrene (2.8%), sabinene (2%) and á-terpineol (0.9%). Treated trees showed a 22% increase in total essential oils as well as a decrease in eucalyptol (65%) and sabinene (0.8%) and an increase in aromadendrene (5%), silvestrene (7.8%) and other ten terpenoids. In addition, treated Eucalyptus showed seven de novo synthesized terpenoids corresponding to carene, á-terpinene, á-fenchene, ã-maaliene, spathulenol and ?-camphenolic aldehyde. Most increased and de novo synthesized terpenoids have potential insecticidal and antimicrobial activities. Trees treated with CHS-828, lycorine, BSO and auranofine and with OC kappa showed an inhibition of increased and de novo synthesized terpenoids. Thus, OC kappa-induced reducing redox status and activation of TRR/TRX system enhance secondary metabolism increasing the synthesis of terpenoids and reprogramming of terpenoid metabolism in Eucalyptus trees. © 2014 by the authors.